Oral substitution treatment of injecting opioid users for prevention of HIV infection. - Gowing, Linda; Farrell, Michael F; Bornemann, Reinhard; Sullivan, Lynn E; Ali, Robert (Cochrane database of systematic reviews (Online), 2011)
Injecting drug users are vulnerable to infection with Human Immunodeficiency Virus (HIV) and other blood borne viruses as a result of collective use of injecting equipment as well as sexual behaviour
Keywords: Administration, Oral; Buprenorphine; HIV Infections; Humans; Methadone; Narcotics; Opioid-Related Disorders; Randomized Controlled Trials as Topic; Risk-Taking; Sexual Behavior; Substance Abuse, Intravenous